The Effect Of Sewage Sludge Ash As Cement Replacement Material On The Mechanical And Chemical Properties Of Mortar Concrete And Terrazzo Tiles - Md Jamil, Mohamad Nazli (2017)
Sewage sludge is a residual from wastewater treatment plant. Nowadays, the large production in sewage sludge quantity is led by the rapid development of sewage treatment plant. This large amount of sewage sludge is generated continuously and has caused in limitation of the disposal area. Hence, an alternative way must be sought out to reuse the sewage sludge for sustainable development. The main objective of this study is to utilize the sewage sludge as a natural admixture in terrazzo tile application. The sewage sludge ash (SSA) was produced by drying and ball-milling process. The optimum incineration temperature of SSA was determined by incinerating the SSA at varying temperature ranging from 500 – 1000oC an with interval of 100oC respectively and mixed as mortar. The physical and chemical properties of each mortar were tested. From the results of the tests, the incinerated temperature of SSA at 900oC (SSA900) was chosen as optimum incineration temperature. Then, concrete mixture with the replacement of SSA900 was casted to determine the ideal percentage amount. The engineering properties and heavy metal concentration were tested. As a result, the concrete with 15% of SSA900 replacement was chosen as an ideal percentage of replacement because it showed the positive outcome for the most of the tests. The performance of SSA terrazzo tiles were examined by testing on breaking strength, water absorption and skid resistance for replacement of 0, 5, 10, 15 and 20%. According to MS 738:1981, the minimum breaking strength is 3.0 MPa, the capillary and total absorption must not exceed of 0.4 g/cm2 and 8% respectively. The terrazzo tile specimens passed the standard requirement. Plus, the tiles were also classified as extremely low in slip potential as compared to United Kingdom Slip Resistance Group (USRG, 2011).